Bridging Culture and Cognition: Deep Learning Strategies in Local-Wisdom-Based IPAS Classrooms - Hasan, Hasan; H, Nursalam; Syamsuddin, Agustan (PPSDP International Journal of Education, 2025)
Global educational reforms increasingly emphasize critical thinking, yet Indonesian elementary schools continue to face challenges in realizing this shift within the Merdeka Curriculum. A key gap persists between curriculum expectations and classroom practice, especially in integrating local wisdom with deep learning approaches. This descriptive qualitative study involved 41 teachers and 77 students through interviews, focus group discussions, observations, and document analysis, framed by the FRISCO reasoning model. The findings show that teachers understand core deep learning principles linking, reflection, and evidence-based reasoning but their implementation is constrained by limited time, uneven technological access, and varying student readiness. Integrating local wisdom through environmental practices, folklore, and cultural traditions significantly increased student engagement and improved critical thinking (N-gain = 0.47), although technology remained underutilized for inquiry-based tasks. These results underscore the need for continuous professional development and the design of culturally grounded learning resources that synergize local content, the FRISCO framework, and technology to achieve curriculum goals. The novelty of this study lies in its holistic integration of cultural knowledge, deep learning pedagogy, and a structured reasoning framework within the Merdeka Curriculum context. Its contribution provides empirical evidence and a conceptual model for developing context-responsive IPAS learning designs that connect technology, culture, and higher-order thinking.